Case Report: Evidence-based case management of ECMO treatment for children with severe lung abscess complicated with bronchopleural fistula - Dan, Li; Yuqian, Meng (Frontiers in Pediatrics, 2025)
This report details an evidence-based nursing management protocol for pediatric cases of severe lung abscess complicated by bronchopleural fistula treated with extracorporeal membrane oxygenation (ECMO). Evidence-based targeted nursing interventions were implemented, including: prone position ventilation care, closed-chest drainage care, bronchial blocker monitoring and care, ECMO cannulas management and hemorrhage control, and innovative measures to prevent pressure injuries related to tubing and devices, The patient underwent 16 days of ECMO support, spent 58 days in the ICU, and was discharged after a total hospital stay of 70 days with full recovery. Follow-up at 3 months post-discharge confirmed excellent pulmonary function restoration.